Analisis Tingkat Kepuasan Pemustaka Terhadap Kinerja Pustakawan di Perpustakan Daerah Kabupaten Sukabumi - Neni Apriyani; Laksmi dewi; Dini Suhardini (Institut Agama Islam Negeri (IAIN) Curup, 2021)
User service is an important element in the library. Libraries should provide the best services to the users or what is often called as excellent services. The excellent service really needs to be supported by the high performance of the librarian. So the users can feel satisfaction from the service thet get. This study aims to determine the level of the user’s satisfaction to the librarian’s performance in Perpustakaan Daerah Kabupaten Sukabumi and whether users have experienced unfavourable treatment due to the librarian’s attitude. The method used in this research is quantitative survey research. The data was collected was through filling out the google form questionnaire. The sample of this research is 40 users who are a registered users in Perpustakaan Daerah Kabupaten Sukabumi. The result showed that the average score of user’s satisfaction was 3.48 which mean that the users were satisfied with the librarian’s performance. 70% of respondent stated that the librarian had worked professionally and 30% of respondent stated that they have experienced inappropriate treatment from the librarian in the form of unfriendly, indifferent, and slow in providing service.